4 The hidden burden of Hepatitis C related advanced liver disease in the community. (5th April 2017) - Iqbal, N; Murphy, C; McHugh, T; Singleton, A; Keating, S; Flanagan, J; Hawthorne, G; Crowley, D; Gallagher, H; Savage, F; Maloney, J; Lambert, JS; et al.
Abstract : Background: In Ireland there are large numbers of HCV+ve patients receiving methadone in drug treatment centre (DTCs) who do not attend hepatology services. Most of these patients have never had their liver disease staged. Fibroscan (FS) is a non-invasive tool to assess liver stiffness which correlates closely with hepatic fibrosis. Clinically relevant cut-offs are 8.5 kPa (access to DAAs in Ireland), 25 kPa (significant portal hypertension) and 35 kPa (10%–20% risk of decompensation per year). Aim: To use FS to risk stratify patients receiving methadone in Dublin DTCs. To determine the impact of active alcohol consumption on FS score. Method: We performed FS on sequential clients receiving methadone in the six larger Dublin DTCs regardless of their HCV status. Clients were also asked regarding alcohol intake and grouped as being –abstinent or not abstinent. Results: A total of 618 consecutive patients (75% male, mean age 38±7.2) were assessed. HCV status was known in 91% (561) of patients with 70% (391) being HCV+ve. The mean FS score was higher in HCV+ve patients than HCV–ve (11.0 kPa ±12.4 vs 5.6 kPa ±4.0;p=0.001). In HCV+ve group, patients that drank alcohol (35%) had a higher score than those that were abstinent (13.2 kPa ±16.4 vs 9.7 kPa ±9.9;p=0.02). There were 128 (33% of total cohort) HCV+ve patients with FS ≥8.5 kPa, 34 (9%) with FS ≥25 kPa and 21 (5%) with FS ≥35 kPa. Conclusions: This study has identified a large number of HCV+ve patients that do not attend hepatology services yet qualify for DAAs. Within this group there are significant numbers of patients at high risk of decompensation. On-going alcohol use is associated with a significantly higher FS score.